2010
DOI: 10.1038/jhg.2010.144
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 rare variants in UK multiple adenoma and early-onset colorectal cancer patients

Abstract: We examined the influence that rare variants and low-frequency polymorphisms in the cancer candidate gene CCND1 have on the development of multiple intestinal adenomas and the early onset of colorectal cancer. Individuals with o100 multiple polyps and patients with colorectal cancer diagnosed before 50 years of age were recruited in UK, and screened for sequence changes in the coding and regulatory regions of CCND1. A set of about 800 UK control individuals was genotyped for the variants discovered in the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The conclusion is that these variants may well be pathologically relevant, but that the in silico approaches are not yet adequate to detect this. The low-frequency variants (MAF between 1 and 5%) do not appear to influence susceptibility to CRC, as we described earlier for CCND1 36. It is clear that further research is needed to evaluate more fully the role of low-frequency variants in cancer 37.…”
Section: Discussionsupporting
confidence: 54%
“…The conclusion is that these variants may well be pathologically relevant, but that the in silico approaches are not yet adequate to detect this. The low-frequency variants (MAF between 1 and 5%) do not appear to influence susceptibility to CRC, as we described earlier for CCND1 36. It is clear that further research is needed to evaluate more fully the role of low-frequency variants in cancer 37.…”
Section: Discussionsupporting
confidence: 54%
“…Various studies have shown the role of cyclin D1 protein in neoplastic transformation and progression of variety of cancers 28 , 29 . In ISCC of CC, there is discrepancy in the expression of Cyclin D1 as few authors reported the elevated levels 14 , 30 and others reported the decreased levels 14 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism has been investigated in studies on ovarian, uterine, cervical ( 23 , 24 ) and breast cancer susceptibility alleles in European Caucasians ( 25 , 26 ), however no clear correlations have been identified. Studies into the c.669C>T variant in colorectal cancer in the UK population led to the conclusion that rare variants of the CCND1 gene are risk factors for colorectal cancer, with considerably larger effects compared with common polymorphisms, and as such should be systematically evaluated in susceptibility studies ( 27 , 28 ). The frequency of the c.669C allele in Caucasians is ~96% and the frequency of the minor allele, c.669T, is 4% ( 29 ).…”
Section: Discussionmentioning
confidence: 99%